Determinants of Self-Efficacy and Employee Performance in the Banking Industry - Primadi Candra Susanto; Haikal Akbari Setiawan; Andri Yandi (Greenation International Journal of Economics and Accounting, 2023)
Aims to prove that self-efficacy is a mediating variable on employee performance in an organization, especially in the banking industry, The research methodology used was qualitative using variable-relevant journal mini-reviews of papers and will be completed later in this study. Results of research from various scientific articles, with the existence of competency, mentoring, and self-efficacy variables in the banking industry environment it is thought to influence employee performance, also by strengthening the research results from existing scientific articles, the increase in self-efficacy is proven by literature studies as well as employee performance which has been described and answers from literature studies of scientific articles prove and researchers want to strengthen the results of research that has been carried out. The recommendations are general in nature because the object here has not been determined by the name of the bank and only describes the results of existing research, and can also provide further research by other researchers in the future with multiple linear regression testing.